Physical Agents and Therapeutic Modalities: Main Concepts Implicated in Physiotherapy Treatment Prescription and Into Advanced Physical Therapy Practice - Gustavo Argenis; Sandra Juárez (European Scientific Journal, ESJ, 2023)
Background: physical agents and therapeutic modalities; two concepts that there is no agreement on their definitions. This leads to a complex phenomena of cognitive construction about what the Physiotherapist are qualified, and required to do. Purpose: to know about the context, conceptualization and updating of both terms. Methods: an electronic search was carried out in the most pertinent databases (PEDro, PubMed, ClinicalKey and OTSeeker). The search strategy was performed in three languages (English, Spanish, and Portuguese), based on preferred reporting items for systematic reviews and meta-analyses methodology (PRISMA). The keywords used for the search were “Physical Agents” AND “Physiotherapy”; “Therapeutic Modalities” AND “Physiotherapy”. Subsequently, an advanced filtering was carried out through the Scale for the Assessment of Narrative Review Articles (SANRA). Results: in PubMed there was a result of 8665 studies displayed but only 3 were accepted; in PEDro only 53 results were obtained, 1 of them was accepted and 1 was eliminated because it was repeated. In ClinicalKey there were a total of 1012 results but none were accepted, and in OTSeeker no search results were founded. On the other hand, there were 15 bibliographies that was aviability and were accessed, which only 5 of them met the inclusion criteria. Conclusions: findings shows a serious issue in terms of conceptualizing what a physiotherapist must do on its professional practice. It could be assumed that they may be two concepts that do not put forward a certain importance from the academic, scientific and/or clinical practice perspective.